A new perspective on the genetics of keratoconus: why have we not been more successful?. (4th March 2018) - Valgaeren, Hanne; Koppen, Carina; Van Camp, Guy
ABSTRACT: Twin studies and family studies suggest an important genetic basis for keratoconus (KC). Involvement and association of several genes with the disease has been reported. Additionally, genes associated with central corneal thickness (CCT) and corneal curvature (CC) via genome-wide association studies (GWAS), also potentially underlie KC. Although a long list of genes has been reported for KC, the evidence for a pathogenic role for most genes remains limited. Furthermore, if the involvement of the reported genes in KC development can be proven, they only account for a limited number of patients. VSX1, ZNF469, SOD1, and miR184 have been most frequently investigated, but only mutations in miR184 indisputably underlie corneal abnormalities. For the three other genes, analysis of the minor allele frequencies (MAF) in public databases argues against a pathogenic role for most reported variants. For the remainder of variants, functional evidence is needed to prove their contribution to the pathogenesis. Despite the large amount of studies, clear results remain rare. A possible explanation for the cumbersome gene-identification is that genetic defects underlying KC are located in regions that are understudied (such as non-coding regions) or that KC is not as monogenic (= one gene with large effect size) as initially considered. Since many of the applied research strategies can only identify large effect mutations, strategies to identify variants with smaller effect sizes might lead to more progress in KC research.